2020
DOI: 10.1186/s41984-020-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day clinical outcome of traumatic brain injury patients with acute extradural and subdural hematoma: a cohort study at Mulago National Referral Hospital, Uganda

Abstract: Background: Increasing traumatic brain injury (TBI) has paralleled the need for decompression surgery for acute subdural (ASDH) and acute extradural haematoma (AEDH). Knowledge of key determinants of clinical outcomes of such patients is mandatory to guide treatment protocols. Objective: To determine the 30-day clinical outcomes and predictor variables for patients with extra-axial hematomas at Mulago National Referral Hospital in Uganda. Methods: Prospective observational cohort study of 109 patients with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 28 publications
3
33
3
Order By: Relevance
“…The most common cause of injury was road traffic collision (64.7%) followed by violence from assault and falls from height. These findings are similar to those of ( Ssebakumba et al, 2020 ) who in their study of subdural and extradural hematomas at Mulago National Referral Hospital in Uganda found that 52.6% were caused by road traffic crashes. Also in a study of causes of unintentional TBIs, Zia et al (2019) found that these were mainly due to road traffic crashes (88.9%) and falls (11.1%).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The most common cause of injury was road traffic collision (64.7%) followed by violence from assault and falls from height. These findings are similar to those of ( Ssebakumba et al, 2020 ) who in their study of subdural and extradural hematomas at Mulago National Referral Hospital in Uganda found that 52.6% were caused by road traffic crashes. Also in a study of causes of unintentional TBIs, Zia et al (2019) found that these were mainly due to road traffic crashes (88.9%) and falls (11.1%).…”
Section: Discussionsupporting
confidence: 91%
“…This compares with similar studies done in Uganda. In a study by Ssebakumba et al (2020) , the median age affected by TBI was 29 years (IQR 23–36) with a male:female ratio of 10:1. Another study by Tran et al (2015) found that males aged 15–29 years comprised the predominant demographic with a male:female ratio of 4.5:1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations